المدقق في الجزائر بين إشكالية الالتزام الأخلاقي والمسؤولية المهنية - زوهري, جليلة; بن عزة, محمد أمين (جامعة الوادي University of Eloued, 2021)
من خلال هذه الورقة البحثية سلطنا الضوء على أهمية و ضرورة التزام المدققين بمعايير السلوك الأخلاقي و المهني , و الامتثال لقواعد الأداء الميداني و هذا ما ينعكس على جودة و مصداقية التقارير النهائية. و بناءا على نتائج الدراسة الاستبيانية اتضح بأن مهنة التدقيق في الجزائر لا ترقى إلى التزام مزاوليها بمعايير و شروط المهنة المعمول بها وفق الأطر القانونية و ذلك باستشهاد الجهات المتعاملة مع المدققين في الميدان ( المؤسسات الاقتصادية ,المالية, الضريبية.....) Through this research paper, we shed light on the importance and necessity of auditor’s adherence to standards of ethical and professional behavior, and compliance with field performance rules, and this is reflected in the quality and reliability of the final reports.And based on the results of the survey, the questionnaire revealed that the auditing profession in Algeria does not live up to the commitment of its practitioners to the standards and conditions of the profession in force in accordance with the legal frameworks, by citing the parties dealing with auditors in the field (economic, financial, tax …..).
Auditor in Algeria between the problem of ethical commitmentand professional responsibility - A field study of a sample of professionals in the field of accounting and finance in Algerian institutions -
مقال
Keywords: معايير التدقيق ,المدقق, الالتزام الأخلاقي, المسؤولية المهنية, الرقابة الداخلية.; Auditing standards, auditor, ethical commitment, professional responsibility, Internal Control.